Giải:
Do \(a\in Z^+\Rightarrow5^b=a^3+3a^2+5>a+3=5^c\)
\(\Rightarrow5^b>5^c\Leftrightarrow b>c\Leftrightarrow5^b⋮5^c\)
\(\Rightarrow\left(a^3+3a^2+5\right)⋮\left(a+3\right)\)
\(\Rightarrow a^2\left(a+3\right)+5⋮\left(a+3\right)\)
Mà \(a^2\left(a+3\right)⋮\left(a+3\right)\) \([\)do \(\left(a+3\right)⋮\left(a+3\right)\)\(]\)
\(\Leftrightarrow5⋮a+3\Rightarrow a+3\inƯ\left(5\right)=\left\{\pm1;\pm5\right\}\left(1\right)\)
Do \(a\in Z^+\Leftrightarrow a+3\ge4\left(2\right)\)
Kết hợp \(\left(1\right)\) và \(\left(2\right)\) ta có:
\(a+3=5\Rightarrow a=5-3=2\)
Thay \(a=2\) vào đẳng thức ta được:
\(2^3+3.2^2+5=5^5\Leftrightarrow25=5^b\Leftrightarrow b=2\)
\(2+3=5^c\Leftrightarrow5=5^c\Leftrightarrow c=1\)
Vậy \(\left(a,b,c\right)=\left(2;2;1\right)\)